2018
DOI: 10.1371/journal.pone.0193991
|View full text |Cite
|
Sign up to set email alerts
|

Fresh red blood cells transfusion protects against aluminum phosphide-induced metabolic acidosis and mortality in rats

Abstract: BackgroundAluminum phosphide (AlP) is used as pesticide in some countries for protection of stored grains. Human poisoning with AlP due to suicide attempt or accidental environmental exposure is associated with very high mortality partially due to development of severe metabolic acidosis. Previous studies have shown that hemoglobin has high buffering capacity and erythrocytes can potentially be used for management of metabolic acidosis. The aim of this study was to evaluate the effect of fresh packed red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Concerning ECG intervals, QTc interval was prolonged in all ALP intoxicated patients and ZnP intoxicated patients with moderate symptoms. In agreement with the current study, several studies reported prolonged QTc interval accompanied with either bradycardia or tachycardia following acute exposure to metal phosphides (Lionate et al, 2004;Jafari et al, 2015;Taghaddosinejad et al, 2016;Asghari et al, 2017 andRahimi et al, 2018). Wide QRS complex was observed in 20.2 % of the studied patients.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning ECG intervals, QTc interval was prolonged in all ALP intoxicated patients and ZnP intoxicated patients with moderate symptoms. In agreement with the current study, several studies reported prolonged QTc interval accompanied with either bradycardia or tachycardia following acute exposure to metal phosphides (Lionate et al, 2004;Jafari et al, 2015;Taghaddosinejad et al, 2016;Asghari et al, 2017 andRahimi et al, 2018). Wide QRS complex was observed in 20.2 % of the studied patients.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the high mortality rate caused by AlP poisoning, underlying mechanisms of AlP toxicity are still not well known. It seems that released phosphine from AlP in the presence of water or gastric acid is responsible for the toxic effects of AlP . In most cases, the mortality rate has been reported with rice pill is more than 50% .…”
Section: Discussionmentioning
confidence: 99%
“…It seems that released phosphine from AlP in the presence of water or gastric acid is responsible for the toxic effects of AlP. 3,19,30,31 In most cases, the mortality rate has been reported with rice pill is more than 50%. 5,32,33 In our study, while selegiline-treated rats (1 mg/kg) induced better survival (only in AlP 12 mg/kg), other doses of selegiline did not change the survival time in AlP-poisoned rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations